Autologous stem cell transplantation with in vivo purged progenitor cells shows long‐term efficacy in relapsed/refractory follicular lymphoma. Issue 3 (March 2015) - Arcaini, Luca; Morello, Lucia; Tucci, Alessandra; Rusconi, Chiara; Ladetto, Marco; Rattotti, Sara; Bonfichi, Maurizio; Bottelli, Chiara; Gabutti, Cristina; Bernasconi, Paolo; Varettoni, Marzia; Gotti, Manuel; et al.
<x xml:space="preserve">Abstract</x> High‐dose chemotherapy with autologous stem cell transplantation (ASCT) has been shown effective in the control of relapsed/refractory follicular lymphoma. We evaluate the long‐term outcome of patients with relapsed or refractory follicular lymphoma treated with ASCT with in vivo purged progenitors cells. We report the long‐term results of a prospective multicenter phase 2 trial on 124 relapsed/refractory follicular lymphoma patients treated with a program of anthracycline‐based debulking chemotherapy, immunochemotherapy, mobilization of in vivo purged PBSC followed by ASCT. Median age was 52 years; 14% of patients had grade 3A histology. Debulking chemotherapy produced CR in 16% and PR in 71%, while 13% of patients progressed. After rituximab, cyclophosphamide, vincristine, prednisone (R‐COP), CR was obtained in 60% and PR in 35%; 118 patients successfully mobilized PBSC and 117 proceeded to ASCT. The harvest in all the 32 molecularly informative patients was bcl‐2 negative. TRM was 0%. The 5‐year PFS was 54% and the 5‐year OS was 83%. After a median f‐up of 6.7 years (range 1.5–13.6), 54% are still in CR. These data show that prolonged PFS is achievable in relapsed/refractory patients with high dose autologous transplantation of in vivo purged progenitor cells. Am. J. Hematol. 90:230–234, 2015. © 2014 Wiley Periodicals, Inc.